Testicular cancer with poor prognosis – only BEP? - Świątoniowski, Grzegorz; Brużewicz, Szymon (Contemporary Oncology/Współczesna Onkologia, 2007)
Relatively good prognosis is characteristic for the germ cell tumors (GCT). Nevertheless, successful treatment with standard therapy is observed only in 50% of patients with high- and intermediate-risk GCT according to the classification of Germ Cell Cancer Collaborative Group (IGCCCG). The results of recent studies oriented towards the improvement of therapeutic results in GCT patients are described in present paper. We have underlined the potential importance of the intensive, non-myeloablative, protocols of alternate chemotherapy used in poor-prognosis GCT patients. Recent two III phase trials revealed that treatment with high-dose chemotherapy with subsequent autologous hematopoietic stem-cell rescue did not improve the survivals compared to conventional therapy. Consequently, there is a need for further studies on the optimization of treatment in poor-prognosis GCT patients.